A novel possible strategy for the management of petrol sniffing addiction in adolescents. (12th November 2010) - Ghanizadeh, Ahmad; Mosallai, Sharif
Abstract : Since the 1950s there have been many reports on petrol addiction, mostly describing the practice of petrol sniffing and its acute and chronic physical and psychological effects. To the authors' knowledge, none have described the use of opiates to manage and control this addiction. We report the case of an 18-year-old boy who self-managed his petrol addiction. He had been inhalant sniffing since the age of 5 and petrol sniffing since the age of 15, and had undergone different treatments in unsuccessful efforts to break his addiction. However, he has now stopped sniffing petrol after taking tramadol 100 mg/day and methadone 10 mg/day. This case report suggests that tramadol and methadone can be used for the management of petrol addiction.